A promising Ni-Fe bimetallic anode for intermediate-temperature SOFC based on Gd-doped ceria electrolyte - Fu, C. F. (2012)
Anode supported solid oxide fuel cells (SOFC) based on Ni–Fe bimetal and gadolinia-doped ceria (GDC) composite anode were fabricated and evaluated in the intermediate- and low-temperature range. Ni0.75Fe0.25-GDC anode substrate and GDC electrolyte bilayer were prepared by the multi-layered aqueous tape casting method. The single cell performance was characterized with La0.6Sr0.4Co0.2Fe0.8O3-GDC (LSCF-GDC) composite cathode. The maximum power density reached 330, 567, 835 and 1333 mW cm−2 at 500, 550, 600 and 650 °C, respectively. Good long-term performance stability has been achieved at 600 °C for up to 100 h. The improved single cell performance was achieved in the reduced temperature after the long-term stability test. The maximum power density registered 185 and 293 mW cm−2 at 400 and 450 °C, respectively. The impedance spectra fitting results of the test cell revealed that the improved cell performance was attributed to the much lower electrochemical reaction resistance. XRD and SEM examination indicated that the outstanding performance of the single cell seemed to arise from the optimized composition and excellent microstructure of Ni0.75Fe0.25-GDC anode, as well as the improved stability of the anode microstructure with prolonged testing time.